ANALISIS MANAJEMEN RISIKO PEMBIAYAAN PADA PT. LKM MAHIRAH MUAMALAH SYARIAH KOTA BANDA ACEH - Husna, Hittatun; Mutia, Evi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to analyze the implementation of financing risk management at PT. LKM Mahirah Muamalah Syariah of Banda Aceh City. This research using a qualitative descriptive methode. The data used are primary data using interview, observation and documentation techniques. The results of this study indicate that the implementation of financing risk management at PT. LKM Mahirah Muamalah Syariah has been implemented well. This is evidenced by the theory and its application in accordance with the rules stipulated by the Financial Services Authority Regulation (PJOK). The four stages in financing risk management, namely the identification, measurement, monitoring and risk control stages are carried out very prudently. The implementation of financing risk management on credit risk, which is seen from the risk of problem financing, is concluded that it is well managed. This can be seen in the decrease in the percentage of the NPF ratio for each period, there is 2.90% in 2019 to 1.88% in 2020. The implementation of risk management in market risk is also concluded as good. It can be concluded that the two risks above do not have a major effect on PT. LKM Mahirah Muamalah Syariah